Metals and cholesterol: two sides of the same coin in Alzheimer’s disease pathology - Wong, Bruce X.; Hung, Ya Hui; Bush, Ashley I.; Duce, James A. (Frontiers in Aging Neuroscience, 2014)
Alzheimer’s disease (AD) is a multifactorial neurodegenerative disease. It begins years prior to the onset of clinical symptoms, such as memory loss and cognitive decline. Pathological hallmarks of AD include the accumulation of β-amyloid in plaques and hyperphosphorylated tau in neurofibrillary tangles. Copper, iron and zinc are abnormally accumulated and distributed in the aging brain. These metal ions can adversely contribute to the progression of AD. Dysregulation of cholesterol metabolism has also been implicated in the development of AD pathology. To date, large bodies of research have been carried out independently to elucidate the role of metals or cholesterol on AD pathology. Interestingly, metals and cholesterol affect parallel molecular and biochemical pathways involved in AD pathology. The possible links between metal dyshomeostasis and altered brain cholesterol metabolism in AD are reviewed.